2018
DOI: 10.1111/jpi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic analysis of the melatonin biosynthesis pathway using chemical labeling coupled with liquid chromatography‐mass spectrometry

Abstract: Characterization of the melatonin (MLT) biosynthesis pathway in plants is still limited. Additionally, a metabolomic analysis of MLT biosynthesis in plants is still a challenge due to analyte structural and chemical diversity, low analyte abundances, and plant matrix complexities. Herein, a sensitive liquid chromatography‐mass spectrometry (LC‐MS) method enabling the simultaneous determination of seven plant MLT biosynthetic metabolites was developed. In the proposed strategy, the targeted metabolites, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
0
28
0
2
Order By: Relevance
“…This alternative pathway for melatonin synthesis has been confirmed in plants (48). In that study, the results indicated that during normal condition, a majority of melatonin was the product of ASMT as the last enzyme; however, under stressful conditions, the major part of melatonin was generated by catalytic activity of SNAT as the final enzyme (49).…”
Section: Fig 2 Localization Of Snat In Rat Choroid Plexus Endothelimentioning
confidence: 54%
“…This alternative pathway for melatonin synthesis has been confirmed in plants (48). In that study, the results indicated that during normal condition, a majority of melatonin was the product of ASMT as the last enzyme; however, under stressful conditions, the major part of melatonin was generated by catalytic activity of SNAT as the final enzyme (49).…”
Section: Fig 2 Localization Of Snat In Rat Choroid Plexus Endothelimentioning
confidence: 54%
“…In each step, multiple isogenes participate in precursor synthesis; for this reason, it is difficult to generate melatonin knockout plants. Due to the low catalytic efficiency of the final two enzymes (SNAT and ASMT), plant melatonin levels are extremely low; therefore, precise quantification of melatonin levels remains challenging, even with the use of cutting-edge liquid chromatography-mass spectrometry (LC-MS) analytical tools [14,30]. However, plant melatonin synthesis can be induced in response to various stimuli, including pathogen infection and cadmium treatment [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low catalytic efficiency of the final two enzymes (SNAT and ASMT), plant melatonin levels are extremely low; therefore, precise quantification of melatonin levels remains challenging, even with the use of cutting-edge liquid chromatography-mass spectrometry (LC-MS) analytical tools [14,30]. However, plant melatonin synthesis can be induced in response to various stimuli, including pathogen infection and cadmium treatment [30,31]. Among many candidates, cadmium is optimal for eliciting melatonin synthesis in rice [32]; however, it cannot induce melatonin production under dark conditions [33].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, tryptophan and intermediate in rice samples increased signicantly aer treated with different concentrations of cadmium in comparison to the control. 32 In this way, the increase in the levels of four tryptophan biosynthesis-related DAPs (Q9FFW8, Q94JT5, Q42529, F4K0T5) under heat stress treatment in the present study might contribute to the enhancement of melatonin in mustard sprouts.…”
Section: Discussionmentioning
confidence: 55%